Widespread and sustained target engagement in Huntington's disease minipigs upon intrastriatal microRNA-based gene therapy - Vallès, Astrid; Evers, Melvin M; Stam, Anouk; Sogorb-Gonzalez, Marina; Brouwers, Cynthia; Vendrell-Tornero, Carlos; Acar-Broekmans, Seyda; Paerels, Lieke; Klima, Jiri; Bohuslavova, Bozena; Pintauro, Roberta; Fodale, Valentina; et al. (Science translational medicine, 2021)
Huntingtin (HTT)-lowering therapies hold promise to slow down neurodegeneration in Huntington's disease (HD). Here, we assessed the translatability and long-term durability of recombinant adeno-associated viral vector serotype 5 expressing a microRNA targeting human HTT (rAAV5-miHTT) administered by magnetic resonance imaging-guided convention-enhanced delivery in transgenic HD minipigs. rAAV5-miHTT (1.2 × 1013 vector genome (VG) copies per brain) was successfully administered into the striatum (bilaterally in caudate and putamen), using age-matched untreated animals as controls. Widespread brain biodistribution of vector DNA was observed, with the highest concentration in target (striatal) regions, thalamus, and cortical regions. Vector DNA presence and transgene expression were similar at 6 and 12 months after administration. Expression of miHTT strongly correlated with vector DNA, with a corresponding reduction of mutant HTT (mHTT) protein of more than 75% in injected areas, and 30 to 50% lowering in distal regions. Translational pharmacokinetic and pharmacodynamic measures in cerebrospinal fluid (CSF) were largely in line with the effects observed in the brain. CSF miHTT expression was detected up to 12 months, with CSF mHTT protein lowering of 25 to 30% at 6 and 12 months after dosing. This study demonstrates widespread biodistribution, strong and durable efficiency of rAAV5-miHTT in disease-relevant regions in a large brain, and the potential of using CSF analysis to determine vector expression and efficacy in the clinic.
Keywords: Animals; Huntingtonova nemoc; Swine, Miniature; genetická terapie; Tissue Distribution; lidé; miniaturní prasata; prasata; genetické vektory; protein huntingtin; modely nemocí na zvířatech; Huntington Disease; Swine; mikro RNA; Huntingtin Protein; tkáňová distribuce; Disease Models, Animal; MicroRNAs; Genetic Therapy; zvířata; Genetic Vectors; Humans